Co-Creation as a Response to Functional Complexity in Slum-Prone Coastal Areas: The Case of Oeba, Kupang City - Salsabila, Sophia; Roychansyah, Muhammad Sani (Universitas Islam Sultan Agung Semarang, 2025)
ABSTRACTThis study discusses the complexity of overlapping functions in the Oeba Coastal Area due to the lack of proper planning and governance. The slum problems occurring in the Oeba Coastal Area are not only caused by physical problems but are also related to the economic and social problems of the local community. This research employs a qualitative descriptive method to understand the condition of the area through a participatory approach. In each stage of the research, four co-creation stages are used to facilitate collaboration among stakeholders, starting from problem identification, discussion sessions, formulation of planning alternatives, to the design stage. In its implementation, it was found that the main cause of urban decay in the Oeba Coastal Area is social aspects, which then affect the economic and environmental aspects of the area. The behavior of the surrounding community and the government's lack of firmness in managing the area have led to a decline in environmental quality. The use of the co-creation method has proven effective in involving the community in every stage of planning, resulting in a more contextual and inclusive design.Keywords: Co-Creation, Functional Complexity, Kupang City, Participatory Planning, Slum Area ABSTRAKStudi ini membahas kompleksitas fungsi yang saling tumpang tindih di Kawasan Pesisir Oeba akibat tidak adanya perencanaan dan tata kelola yang baik. Permasalahan kekumuhan yang terjadi di Kawasan Pesisir Oeba tidak hanya disebabkan oleh permasalahn fisik, tetapi juga terkait permasalahan ekonomi dan sosial masyarakat setempat. Penelitian ini menggunakan metode deskriptif kualitatif untuk memahami kondisi kawasan dengan pendekatan partisipatif. Dalam setiap tahapan penelitian digunakan 4 tahapan co-creation untuk menjembatani kolaborasi antar stakeholder, mulai dari identifikasi permasalahan, sesi diskusi, perumusan alternatif perencanaan, hingga tahap desain. Dalam pelaksanaanya, ditemukan utama kekumuhan di Kawasan Pesisir Oeba disebabkan oleh aspek sosial yang kemudian mempengaruhi aspek ekonomi dan lingkungan kawasan, dimana perilaku masyarakat sekitar dan ketidaktegasan pemerintah dalam tata kelola kawasan menyebabkan penurunan kualitas lingkungan. Penggunaan metode co-creation terbukti efektif dalam melibatkan masyarakat dalam setiap tahapan perencanaan, sehingga menghasilkan desain yang lebih kontekstual dan inklusif.Kata kunci: Co-Creation, Kawasan Kumuh, Kompleksitas Fungsi, Kota Kupang, Perencanaan Partisipatif